Varactor-Tuned Dual-Mode Frequency Discriminator for Instantaneous Frequency Measurements - Moscoso Mártir, Álvaro; Molina-Fernández, Íñigo; Hong, Jiasheng (IEEE European Microwave Week, 2013)
In this paper a novel varactor-tuned frequency discriminator that makes use of two tunable dual-mode microstrip resonators is demonstrated which doubles the discriminator tuning bandwidth. To prove its validity a prototype of the tunable dual-mode microstrip resonator is manufactured and the measured results are used to study the frequency discriminator response. This new approach can cover almost an octave of frequency range from 1.05 to 2 GHz with a sensitivity of 45 V/GHz and 21 V/GHz for the first and second mode, respectively.
Keywords: Microondas